Temu Kembali Bahan Pustaka di Perpustakaan STKIP PGRI Sumbar - Ahmad, Fandi; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2012)
This paper discussed about the retrieval of library materials in the Library STKIP PGRI West Sumatera. This study aimed to determine the process of information retrieval and facets used by user in search of information in the Library STKIP PGRI West Sumatera. Data were collected through observation and interviews with user who come to visit the Library STKIP PGRI West Sumatera. Analyzing the data be descriptive. By analyzing the data, it was concluded the following. First Library STKIP PGRI West Sumatera use classification chart DDC (Dewey Decimal Classification), but in preparation at the library shelf STKIP PGRI West Sumatera not by DDC, but based courses available at STKIP PGRI West Sumatera. The process of finding library materials or books in the library by user STKIP PGRI West Sumatera done by directly looking for library materials or books needed to rack available without using search. User Library STKIP PGRI West Sumatera search for books or library materials required by their respective majors. Both charts are used library classification STKIP PGRI West Sumatera what is known within their user. Â Keywords: retrieval; facet;Â Library STKIP PGRI West Sumatera